PELATIHAN PEMBUATAN GERABAH SEMPE-BALANGA DI NEGERI OUW, KABUPATEN MALUKU TENGAH - Leiwakabessy, Christoffol; Usmany, Jesisca Gloria; Patty, Markus Novel; Sapulette, Mariska Z; Siwalette, Natasha V; Latupapua, Jonathan; Batmomolin, Frans; Meute, Sulce; Letemulu, Martinah M; Sanga, Yuliana; Jambormias, Edizon (PAKEM : Jurnal Pengabdian Kepada Masyarakat, 2023)
Sempe-balanga is a traditional craft that has existed long ago in Ouw and has become a culture in this country. The pottery craftsmen made many changes so that this pottery became more and more known. the lack of interest in women in the country to develop pottery crafts is one of the limiting factors. The purpose of this training is to increase the interest and participation of women to pursue these skills to make these products a source of family income. The training method used is collection through interviews, while the craft development strategy is literature study, observation, and interview. The results of the training showed that many women in this country were interested in learning the culture of sempe-belanga, porna and kenda/plat, and tajela. In addition, there are variations of pottery craft products such as flower pots, wall hangings, angglong, and so on, also given during the training